New interest-sensitive and network-sensitive method for user recommendation - Yan-min SHANG; Peng ZHANG; Ya-nan CAO (Tongxin xuebao)
A new hybrid approach by incorporatin gusers’ interests and users’ friendships together to recommend new friends for target users is proposed.A variation of PageRank—Topic_Friend_PageRank(TFPR) is proposed,which can consider user interests and user friends at same time.Firstly,proposed method uses latent Dirichlet allocation (LDA) to model users’ interests,and weighted-PageRank algorithm to model users’ friendship network,and then merge these two factors into TFPR.This hybrid method models users’ interests and users’ friendships at the same time,and wedemonstrate the effectiveness of proposed hybrid model by using some social network datasets.